Defining some potential nutritional determinants of obesity in adolescent population - Sohani, Amit; Sanjeev, Chincholikar (International Journal Of Community Medicine And Public Health, 2019)
Background: The basic cause of obesity is over nutrition easy and increasing availability of energy-dense, high-calorie foods/snacks and drinks are one of the factors that could significantly affect children’s energy intake. Methods: All adolescent school going boys and girls in the age group between 10 to 19 years were included as per definition of adolescent. 585 students were selected by systematic sample i.e. every third student was included in the study sample. A pretested standardized questionnaire which consisted of questions related to sociodemographic data and nutrition was used to screen the population for determining association between nutrition and obesity. Results: It can be observed that 28.21% students were vegetarian while remaining 71.79% were having mixed diet. It can be observed from the Table 2 that overweight and obesity are not related to frequency of consumption of meal, It can be seen that 30.97% overweight subjects had frequent junk food. There was a significant association between frequency of junk food and prevalence of overweight as well as obesity. 25.73% Students with overweight and obese subjects were frequent sweet eaters. Conclusions: Vegetarian diet or non-vegetarian diet did not have any effect on prevalence of underweight, overweight and obesity in adolescent population. Overweight and obesity are not related to frequency of consumption of meal. There was a significant association between frequency of junk foods, sweets with prevalence of overweight as well as obesity.